Poverty's latent effect on adiposity during childhood: evidence from a Québec birth cohort. Issue 3 (22nd November 2013) - Kakinami, Lisa; Séguin, Louise; Lambert, Marie; Gauvin, Lise; Nikiema, Béatrice; Paradis, Gilles
Abstract : Background: Childhood poverty heightens the risk of obesity in adulthood, but the age at which this risk appears is unclear. We analysed the association between poverty trajectories with body mass index (BMI) Z-scores or the risk of being overweight or obese across four ages (6 years, 8 years, 10 years and 12 years) in childhood. Methods: Data were from the 1998–2010 'Quebec Longitudinal Study of Child Development' cohort (n=698). Poverty was defined using Statistics Canada's thresholds, and trajectories were characterised with a Latent Class Growth Analysis. Multivariable linear and logistic regression models adjusted for sex, whether the mother was an immigrant, maternal education and birth weight. Results: Four income trajectories were identified: a reference group (stable non-poor), and 3 higher exposure categories (increasing likelihood of poverty, decreasing likelihood of poverty or stable poor). Compared with children from stable non-poor households, children from stable poor households had BMI Z-scores that were 0.39 and 0.43 larger than children from stable non-poor households at age 10 years and 12 years, respectively (p<0.05). Compared with children from stable non-poor households, children from stable poor households were 2.22, 2.34, and 3.04 times more likely to be overweight or obese at age 8 years, 10 years and 12 years, respectively (p<0.05). Conclusion: A latency period for the detrimental effects of child poverty on the risk of overweight or obesity was detected. Whether the effects continue to widen with increasing duration of exposure to poverty as the children age should be investigated.